The Teenage Brain: Cognitive Control and Motivation. (April 2013) - Luna, Beatriz; Paulsen, David J.; Padmanabhan, Aarthi; Geier, Charles
Adolescence is associated with heightened mortality rates due in large measure to negative consequences from risky behaviors. Theories of adolescent risk taking posit that it is driven by immature cognitive control coupled with heightened reward reactivity, yet surprisingly few empirical studies have examined these neurobiological systems together. In this article, we describe a series of studies from our laboratory aimed at further delineating the maturation of cognitive control through adolescence, as well as how rewards influence a key aspect of cognitive control: response inhibition. Our findings indicate that adolescents can exert adult-like control over their behavior but that they have limitations regarding the consistency with which they can generate optimal responses compared with adults. Moreover, we demonstrate that the brain circuitry supporting mature cognitive (inhibitory) control is still undergoing development. Our work using the rewarded antisaccade task, a paradigm that enables concurrent assessment of rewards and inhibitory control, indicates that adolescents show delayed but heightened responses in key reward regions along with concurrent activation in brain systems that support behaviors leading to reward acquisition. Considered together, our results highlight adolescent-specific differences in the integration of basic brain processes that may underlie decision making and more complex risk taking in adolescence.